Decrease in Serum Anti-MAG Autoantibodies Is Associated With Therapy Response in Patients With Anti-MAG Neuropathy: Retrospective Study. Issue 1 (January 2022) - Hänggi, Pascal; Aliu, Butrint; Martin, Kea; Herrendorff, Ruben; Steck, Andreas Johann
Abstract : Background and Objectives: The objective of the retrospective analysis was to test the hypothesis that changes in serum anti-myelin-associated glycoprotein (MAG) autoantibodies are associated with clinical response to immunotherapy in patients with anti-MAG neuropathy. Methods: As of January 29, 2020, we used anti-myelin-associated glycoprotein-related search strings in the Medline database to identify studies that provided information on anti-MAG immunoglobulin M (IgM) autoantibodies and clinical outcomes during immunotherapies. The relative change in anti-MAG IgM titers, paraprotein levels, or total IgM was determined before, during, or posttreatment, and the patients were assigned to "responder, " "nonresponder, "' or "acute deteriorating" category depending on their clinical response to treatment. The studies were qualified as "supportive" or "not supportive" depending on the percentage of patients exhibiting an association between relative change of anti-MAG antibody titers or levels and change in clinical outcomes. Results: Fifty studies with 410 patients with anti-MAG neuropathy were included in the analysis. Forty studies with 303 patients supported the hypothesis that a "responder" patient had a relative reduction of anti-MAG antibody titers or levels that is associated with clinical improvements and "nonresponder" patients exhibited no significant change in anti-MAG IgM antibodies. Six studies with 93 patients partly supported, and 4 studies with 26 patients did not support the hypothesis. Discussion: The retrospective analysis confirmed the hypothesis that a relative reduction in serum anti-MAG IgM antibodies is associated with a clinical response to immunotherapies; a sustained reduction of at least 50% compared with pretreatment titers or levels could be a valuable indicator for therapeutic response.